Socio-emotional skills: Educational improvement or controlled education (Revista Contexto & Educação, 2025)
Since the 1990s, Brazilian government projects have reflected policies aimed at expanding capital. This period marks the beginning of our scientific initiation research, which serves as the basis for this article. Throughout the analysis of normative documents, it is clear that policies of international organizations, such as the World Bank and the OECD, have a direct influence on Brazilian educational policies, as the focus is to promote a minimum basic education for workers, with the aim of reducing poverty and inequality. The theme of socio-emotional skills and abilities appears in the school environment alongside cognitive skills. Based on this, the results of the documentary and bibliographic survey are presented, through theses, dissertations and documents, on the Scientific Electronic Library Online, Scielo, and on the Brazilian Library of Theses and Dissertations, BDTD, as well as World Bank documents, intended for Brazil, that deal with Socioemotional Skills and Competencies, HSE, how they approach this topic and the consequences for Brazilian education, with interconnection with higher education and teacher training. The historical milestone is the period from 1990 to 2022. The aim is to demonstrate that this model emphasizes the practical execution and the valorization of skills and competencies within hegemonic pedagogies, distorting the educational function, focusing on technique, on “learning to learn” and on “knowing how to do”, as tools for reproducing utilitarian teaching.
Keywords: International organizations; Skills and Abilities; Capitalist formation